Modeling Chinese Teachers’ Efficacies for the Teaching of Integrated STEM With Interdisciplinary Communication and Epistemic Fluency - Lin, Pei-Yi; Chai, Ching Sing; Di, Weifeng; Wang, Xingwei (Frontiers in Psychology, 2022)
Engineering design is a core activity in integrated science, technology, engineering, and mathematics (STEM) education. During the design process, teachers should possess interdisciplinary communication capacities to collaborate with their peers who are teaching different subjects and have epistemic fluency to comprehend multiple ways of subject matter knowing for the collective design of high-quality integrated STEM (iSTEM) lessons. This is especially so for the online mode of instruction during and after the pandemic. Teachers’ efficacies for interdisciplinary communication and epistemic fluency have rarely been explored. In this study, we aimed to examine primary school, junior high school, and high school STEM teachers’ (N = 483) efficacies for daily instruction, student engagement, interdisciplinary communication, epistemic fluency, and technological pedagogical engineering knowledge (TPEK) and designing integrated STEM instruction. An exploratory factor analysis (EFA) (n = 155) and a subsequent confirmatory factor analysis (CFA) (n = 328) were used to validate the measurement and structural model. Next, a structural equation model (SEM) was employed to examine whether these variables were reliable predictors of teachers’ integrated STEM instruction. The survey was validated with good reliabilities and the structural equation modeling supported most of the hypotheses. Statistically, the results also showed that teachers’ general efficacies for daily teaching and students’ engagement predicted their interdisciplinary communication, epistemic fluency, and TPEK. Teachers’ interdisciplinary communication predicted their epistemic fluency, TPEK, and iSTEM. Teachers’ epistemic fluency also predicted their TPEK and iSTEM. In addition, multi-group analyses were used to test the measurement invariance of the scale and to compare the latent means between the genders and subject matters. The results of the various analyses confirmed that the measurement model appeared to be equivalent across the genders and subject matters examined. Genders and subject matters did not significantly differ in any of the measured variables. The results from this study indicate that teachers’ epistemic fluency and interdisciplinary communication play essential roles in advancing their TPEK and iSTEM. Hence, this study suggests that teacher professional development should focus on enhancing teacher epistemic fluency through interdisciplinary collaboration to support the development of TPEK and iSTEM instruction.